2004
DOI: 10.1159/000081644
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation of Liver Tumors: How to Enlarge the Necrotic Zones?

Abstract: In an attempt to increase necrotic zones in liver tissue by radiofrequency ablation fresh bovine liver was coagulated by means of a needle electrode continuously perfused with NaCl solution. Power output (60 W) and application time (15 min) were kept constant while the perfusion was varied in terms of saline concentration (0.9, 5.85 and 10%) and perfusion rate (40 or 80 ml/h). Our results showed that the use of higher osmolar saline solutions in radiofrequency ablation with perfused needle electrodes did not l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…It is thought that by hydrating the liver to prevent drying and charring, time to roll off can be extended and larger ablations can be created. This rationale has been used experimentally by preinjecting the tumor and surrounding tissue with either hypertonic or isotonic saline; this produces a modest increase in the size of the ablation [20]. Perfusion type needle electrodes are also available for clinical use that have small apertures that allow diffusion of hypertonic or isotonic saline into the surrounding tissues [1].…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that by hydrating the liver to prevent drying and charring, time to roll off can be extended and larger ablations can be created. This rationale has been used experimentally by preinjecting the tumor and surrounding tissue with either hypertonic or isotonic saline; this produces a modest increase in the size of the ablation [20]. Perfusion type needle electrodes are also available for clinical use that have small apertures that allow diffusion of hypertonic or isotonic saline into the surrounding tissues [1].…”
Section: Introductionmentioning
confidence: 99%
“…Once tissues become charred, they can no longer conduct the electrical current and the ablating process ceases 1 . It has been shown experimentally that by injecting solution around the electrode tip that larger ablations can be created in ex vivo and in vivo livers 5 . This has led to the development of the perfusion‐type needle electrodes that are used clinically.…”
Section: Introductionmentioning
confidence: 99%
“…With review of studies treating malignancy with combined RFA and hypertonic saline, only one other study reported combined RFA with hypertonic saline in humans and was done on pulmonary metastatic tumor (from HCC) in one patient [15]. Other studies were done in animals like rabbit liver [12,16] or kidney [17] or porcine liver [18] or done in explanted bovine liver [19][20][21] and all showed that RFA+HS gave better efficiency in creating a large ablation area than does dry RFA. The post procedural complications in our study were comparable between both groups, indicating higher ablation with no additional harmful effects.…”
Section: Current Trends In Biomedical Engineering and Biosciencesmentioning
confidence: 99%